La declaración de inconstitucionalidad del delito del “negacionismo” (artículo 607.2 del código penal español) (2009)
Including the crime of “apology for genocide” in the article 607.2 of the Spanish Criminal Code (SCC) was considered a problem by jurisprudence because it was difficult to harmonize that article with the “overall” apology that appears in article 18.1 SCC.